Overlooking Blanco White's Abolitionist Consciousness: Menéndez Pelayo and Goytisolo. - Krauel, Javier (Hispanic Review)
The purpose of this article is to rethink the modern reception of José María Blanco White's Bosquejo del comercio de esclavos (1814) through an analysis of Marcelino Menéndez Pelayo's chapter on Blanco White in his Historia de los heterodoxos españoles (1880–1882) and Juan Goytisolo's foreword to his anthology Obra inglesa, selecta de sus obras en esta lengua (1972). By drawing on the insights of the "archival turn" taken by contemporary critics, this essay reveals how Menéndez Pelayo's omission of Blanco White's abolitionism had such lasting effects that Goytisolo was unable to rectify it despite his explicit political commitments to human dignity, antislavery, and antiracism. Ultimately, this article shows that Goytisolo failed to treat Blanco White's abolitionist sentiment as a historical topic in its own right because he mounted a political challenge to Menéndez Pelayo's portrayal of Blanco White, but at the same time left untouched the power inscribed in the Catholic polymath's archival narrative.